Working Environment In Nursing: Needs Improvement? - Paz, Julia Del Monte; PogrÃ¡nyivÃ¡, Alicia HanzelikovÃ¡; LÃ³pez, MarÃa Victoria GarcÃa; MartÃnez, Dolores Pomares; FernÃ¡ndez, MarÃa JosÃ© Pardo (Department of Nursing, Faculty of Medicine, Diponegoro University, 2012)
Background: Knowing the quality of life of professionals is important because it is related to job performance, better results, and greater productivity, which results in better patient care. Objective: To know the Professional Quality of Life perceived by the nurses at the Geriatric Hospital of Toledo (Spain). Method: A descriptive cross-section study was employed to measure the Professional Quality of Life of all healthcare nurses (69 in total) at the Geriatric Hospital of Toledo. The questionnaire used as a measuring instrument was the Professional Quality of Life - 35. The data obtained was analyzed by means of: descriptive statistics, single-factor ANOVA variance analysis, T Student tests, and simple and multiple regression analysis. The study was approved by both the research commission and the ethics commission at the Hospital Complex of Toledo. Participation in the study on behalf of the nursing staff was voluntary. Results: In total, 45 responses were obtained (65.2%). The overall mean score measured the perceived Professional Quality of Life to be low. In relation to the three dimensions evaluated in the study, the highest average found was in â€œintrinsic motivation,â€ followed by â€œworkloadâ€, and then â€œmanagement support.â€ In the multivariate analysis, â€œmanagement supportâ€ was shown as the most influential factor in the Professional Quality of Life with a 23% influence (P<0.001), followed by workload with 9% (P = 0.01). Conclusions: The professionals at the participating center perceive their workplace as having an elevated degree of responsibility, a large quantity of work, a high occurrence of rushes and fatigue, and all this with little support on behalf of management. Promotions are scarce or the policies for receiving a promotion are inadequate. The perception of Professional Quality of Life in nursing is low. The obtained results indicate a need for an organizing cultural change based on participation, motivation, and increased management support. Key Words: Work satisfaction, nursing, hospital, care